Optimizing Hydrocortisone Concentration for Skeletal Muscles Differentiation of ADSCs on PLLA Nano-Scaffolds - Mashhadikhan, Maedeh; Soleimani, Masoud; Parivar, Kazem; Yaghmaei, Parichehr (Archives of Advances in Biosciences, 2015)
Skeletal muscle is a highly differentiated tissue with very specific functions which has low potential of regeneration. Skeletal muscle injuries especially in athletes almost have lead to muscular dysfunctions and healing may be prolonged for several years. Therefore, working on skeletal muscle differentiation remained an importance in biomedical researches. Adipose derived stem cells (ADSCs) are novel source of mesenchymal stem cells which are an excellent alternative for satellite cells in in-vitro skeletal muscle differentiation. Differentiation potential of ADSCs on both tissue culture plate (TCP) and also on Poly l-lactide acid (PLLA) electrospun fibrous nano-scaffold which now is widely used at tissue engineering investigations has studied in this research. Scanning electron microscopy (SEM) and Tensile test were performed for evaluating scaffold properties. Hydrocortisone has considered a critical factors for skeletal muscle differentiation while, the recommended concentrations of it for inducing myogenesis in stem cells is yet discussing. Statistical analysis of our results from colorimetric MTT assay for various concentrations of hydrocortisone showed that the concentration of 10-7 mol/L is the optimum dose for myogenic differentiation of murine ADSCs which was used on both TCP and PLLA scaffolds and skeletal myosin fiber formations was confirmed with immunocytochemistry. DAPI staining proved myocytes nuclei and syncytium formations. Our results also showed that ADSCs and PLLA nano-scaffolds are the suitable biomaterials for engineering skeletal muscle tissue.